Rattus hoogerwerfi Chasen 1939 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
680. Hoogerwert’s Sumatran Rat Rattus hoogerwerfi French: Rat de Hoogerwef / German: Hoogerwerf-Ratte / Spanish: Rata de Sumatra de Hoogerwerf Other common names: Atjehan Moutain Rat, Hoogerwerf’s Rat Taxonomy. Rattus hoogerwerfi Chasen, 1939, Blang Kedjeren, 2900 ft (= 885 m), Gunung [euser, Aceh, western Sumatra, Indonesia. Phylogenetic placement of R. hoogerwerfi in Rattus is uncertain, although it might be related to R. korinchi and R. baluensis. Monotypic. Distribution. Highlands of Mt Leuser, NW Sumatra. Descriptive notes. Head-body 165-196 mm, tail 210-257 mm, ear 19-26 mm, hindfoot 36-39 mm; weight 113-153 g. Hoogerwerf’s Sumatran Rat is medium-sized and distinctive, with very soft and long pelage. Dorsum is dark ocherous buffish brown, with many black guard hairs and gray underfur, lighter on sides and blending into ventral pelage. Venteris rufous buff. Juveniles are dullerbrown in color. Feet are thinly covered in short dark brown hair, with silvery hairs around bases of claws. Ears are brown; ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 837, DOI: 10.5281/zenodo.6887260 ...